Estimation of evapotranspiration using a simulation model (Journal of the Bangladesh Agricultural University, 2012)
Practical methods for the accurate estimation of water requirement for irrigated agriculture are essential. Simulation  model is a useful tool to estimate water balance in the crop field. In this study, the BUDGET model was used to  evaluate its performance to simulate water balance in wheat field. The BUDGET model is composed of a set of  validated subroutines describing the various processes involved in water extraction by plant roots and soil water  movement in absence of a water table. The model was run to simulate evapotranspiration values with the actual  observed weather, crop and soil data for three years (2002-2005), obtained from experimental Station of Bangladesh  Institute of Nuclear Agricultural (BINA). The input data of model are separated into four stages and the value of Kc  and root depth are different for each stage. Evaluation of model performance is done with both graphical display and  statistical criteria. The simulated values fall close to 1:1 line, indicating better performance. The statistical parameters  such as standard deviation (SD), standard error (SE), coefficient of variation (CV) of simulated and actual  evapotranspiration values are found 21.07 and 29.23; 4.49 and 6.23; and 38.03 and 50.75, respectively. Both the  standard error and coefficient of variation for simulated values are found lower than the observed values indicating  stability of the model output. The coefficient of determination value (R2 =0.83) is high for this model, which indicates  good simulation performance. The relative error (RE) is 23.28 percent and model efficiency (EF) is 78.95 percent  which means that the simulation of actual evapotranspiration is satisfactory. The value of Index of agreement (IA) is  0.918 which indicates a very good performance of the model. The overall statistical parameters of simulation period  are in satisfactory level. Therefore, the BUDGET model is able to predict actual evapotranspiration for any level of  soil moisture with reasonable accuracy. The model can be used in planning, management and operation of an  irrigation project for judicious use of water with the limited inputs, especially suitable for countries where modeling of  crop yield is needed under water stress conditions.   DOI: http://dx.doi.org/10.3329/jbau.v9i2.11038   J. Bangladesh Agril. Univ. 9(2): 257266, 2011